Prototipo de sistema fotovoltaico híbrido capaz de abastecer de energía a vehículos eléctricos particulares y de estaciones de carga en la ciudad de Loja - Lojan Sánchez, Rodrigo Alexander (2025)
The concept and application of electromobility are crucial in Ecuador, particularly in Loja. A solid technical foundation is required to support the adoption of this mode, maximizing its benefits and mitigating its negative impacts. This work examines the design of stand-alone and grid-connected photovoltaic systems to cover the demand for power from private electric vehicles (cabs) and charging stations. Through surveys and the use of the “Electricity Geoportal (ArcGIS),” accurate data was gathered on the average daily electricity consumption and the technical requirements for connecting both the electric charging station and the two types of electric vehicles used in the taxi service. This platform makes it possible to generate a detailed summary of the charging points and transformers present in specific areas. A technical analysis of the sizing of each photovoltaic system, both independent and grid-connected, was conducted using mathematical models and the PVsyst software. There is a detailed description of how to size the system to meet the load and the connection diagrams, as well as a description of how each component of the system is selected and characterized. Two systems were designed that can be implemented in either a residence connected to the electrical grid or in a rural area without access to the grid. In addition, at the end, an economic analysis is included that covers the costs associated with the implementation and the amortization period of each system. In conclusion, the proposal for a possible implementation with institutions in the city of Loja has been discussed. Key words: Electric vehicles, photovoltaic systems, electromobility, electric vehicle, photovoltaic systems, electromobility, electric vehicle station, surveys, electricity consumption, technical dimensioning, economic analysis, possible implementation.